Archetypes of Climate-Risk Profiles among Rural Households in Limpopo, South Africa - Paumgarten, F.; Locatelli, Bruno; Witkowski, E.T.F. (American Meteorological Society, 2020)
More frequent and intense climate hazards, a predicted outcome of climate change, are likely to threaten existing livelihoods in rural communities, undermining households’ adaptive capacity. To support households’ efforts to manage and reduce this risk, there is a need to better understand the heterogeneity of risk within and between communities. The Intergovernmental Panel on Climate Change revised their climate vulnerability framework to incorporate the concept of risk. This study contributes toward the operationalization of this updated framework by applying a recognized methodology to the analysis of the climate-related risk of rural households. Using a mixed-method approach, including a cluster analysis, it determined and assessed archetypical patterns of household risk. The approach was applied to 170 households in two villages, in different agroecological zones, in the Vhembe District Municipality of South Africa’s Limpopo Province. Six archetypical climate-risk profiles were identified based on differences in the core components of risk, namely, the experience of climate hazards, the degree of exposure and vulnerability, and the associated impacts. The method’s application is illustrated by interpreting the six profiles, with possible adaptation pathways suggested for each. The archetypes show how climate-related risk varies according to households’ livelihood strategies and capital endowments. There are clear site-related distinctions between the risk profiles; however, the age of the household and the gender of the household head also differentiate the profiles. These different profiles suggest the need for adaptation responses that account for these site-related differences, while still recognizing the heterogeneity of risk at the village level.